Impact of treatment adherence and inhalation technique on asthma outcomes of pediatric patients: a longitudinal study - Lizano-Barrantes, Catalina; Garin, Olatz; Mayoral, Karina; Dima, Alexandra L.; Pont, Angels; Caballero-Rabasco, María Araceli; Praena-Crespo, Manuel; Valdesoiro-Navarrete, Laura; Guerra, María Teresa; Bercedo-Sanz, Alberto; Ferrer, Montse (Frontiers in Pharmacology, 2024)
Introduction: We aimed to evaluate the longitudinal relationships, both at between- and within-person levels, that adherence to inhaled corticosteroid-based maintenance treatment and inhalation technique present with symptom control, exacerbations, and health-related quality of life (HRQoL) in children and adolescents with asthma. Methods: Participants (6–14 years old) from the ARCA (Asthma Research in Children and Adolescents) cohort—a prospective, multicenter, observational study (NCT04480242)—were followed for a period from 6 months to 5 years via computer-assisted telephone interviews and a smartphone application. The Medication Intake Survey–Asthma (MIS-A) was administered to assess the implementation stage of adherence, and the Inhalation Technique Questionnaire (InTeQ) was used to assess the five key steps when using an inhaler. Symptom control was measured with the Asthma Control Questionnaire (ACQ), and HRQL was measured with the EQ-5D and the Patient-Reported Outcomes Measurement Information System–Pediatric Asthma Impact Scale (PROMIS-PAIS). Multilevel longitudinal mixed models were constructed separately with symptom control, exacerbation occurrence, EQ-5D, and PROMIS-PAIS as the dependent variables. Results: Of the 360 participants enrolled, 303 (1,203 interviews) were included in the symptom control and exacerbation analyses, 265 (732) in the EQ-5D, and 215 (617) in the PROMIS-PAIS. Around 60% of participants were male subjects, and most of them underwent maintenance treatment with inhaled corticosteroids plus long-acting β-agonists in a fixed dose (73.3%). Within-person variability was 83.6% for asthma control, 98.6% for exacerbations, 36.4% for EQ-5D, and 49.1% for PROMIS-PAIS. At the within-person level, patients with higher adherence had better symptom control (p = 0.002) and HRQoL over time (p = 0.016). Patients with a better inhalation technique reported worse HRQoL simultaneously (p = 0.012), but they showed better HRQoL in future assessments (p = 0.012). The frequency of reliever use was associated with symptom control (p < 0.001), exacerbation occurrence (p < 0.001), and HRQoL (p = 0.042); and boys were more likely to present better symptom control and HRQoL than girls. Conclusion: Our results confirm longitudinal associations at the within-person level of the two indicators of quality use of inhalers: for adherence to maintenance treatment with symptom control and HRQoL, and for the inhalation technique with HRQoL. Although treatment adherence was shown to be excellent, a third of the participants reported a suboptimal inhalation technique, highlighting the need for actions for improving asthma management of the pediatric population.